2001
DOI: 10.1124/mol.59.4.837
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cisplatin Cytotoxicity and Cisplatin-Induced DNA Cross-Links in HepG2 Cells by Regulation of Glutathione-Related Mechanisms

Abstract: Glutathione (GSH), glutathione S-transferase (GST), and glutathione conjugate export pump (GS-X pump) have been shown to participate collectively in the detoxification of many anticancer drugs, including cisplatin. Identification and regulation of the rate-limiting step in the overall system for cisplatin detoxification is of crucial importance for sensitization of human tumor cells to cisplatin. In this study, the GSH content, GST activity, and GS-X pump activity were regulated separately to examine effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
2
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 31 publications
(44 reference statements)
1
61
2
1
Order By: Relevance
“…8 It has been reported that an increase in the expression of GST , together with a high concentration of GSH, was involved in resistance to CDDP. 43,44 The activity of GST in HCT8DDP cells was higher than that in HCT8 cells, which are relatively sensitive to CDDP. 7 But the expression of GST mRNA did not change in HCT8DDP cells transfected with anti --GCSh ribozyme ( data not shown ).…”
Section: Discussionmentioning
confidence: 96%
“…8 It has been reported that an increase in the expression of GST , together with a high concentration of GSH, was involved in resistance to CDDP. 43,44 The activity of GST in HCT8DDP cells was higher than that in HCT8 cells, which are relatively sensitive to CDDP. 7 But the expression of GST mRNA did not change in HCT8DDP cells transfected with anti --GCSh ribozyme ( data not shown ).…”
Section: Discussionmentioning
confidence: 96%
“…Factors described as playing a role in the cisplatin response, including high-mobility group proteins, DNA MMR factors, signaling molecules such as c-jun, c-abl, and p73 (4,10,26,27), and alterations in uptake and inactivation (1,7,8,28), were all thought to act within individual cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the IC 50 of 260 M for megestrol acetate was much higher when compared with 42.8 M for cisplatin (29), which is a widely used anticancer drug for treatment of human malignancies, including HCC. This suggests that the direct effect of megestrol acetate on the growth of HepG2 cells can only be achieved at higher dosages, and high dosages are needed clinically for inhibition of growth of HCC in patients.…”
Section: Discussionmentioning
confidence: 94%
“…The IC 50 for megestrol acetate was calculated by a linear regression. The IC 50 of 260 M for megestrol acetate was much higher when compared with 42.8 M for cisplatin (29), which is a widely used anticancer drug for the treatment of human malignancies, including HCC. Incubation with 200 M megetrol acetate also showed timedependent inhibition on the growth of the human liver tumor cells (Fig.…”
Section: Inhibition Of Growth Of Hepg2 Cells In Vitromentioning
confidence: 99%
See 1 more Smart Citation